PERAN NOTARIS DALAM MEMBERIKAN PENYULUHAN HUKUM TERHADAP PENDIRIAN PERSEROAN TERBATAS - Siska Andriani; M. Hadin Muhjad; Saprudin (LPPM STIH Awang Long, 2023)
Based on Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services (hereinafter referred to as PP Number 24 of 2018 which states that company registration, both individual and non-individual, must be carried out through the OSS system. The development of the process of establishing a Limited Liability Company in accordance with Government Regulation Number 24 of 2018 means that the notary must also be able to following changes by properly understanding the OSS system, especially in KBLI registration, this means that the role of notaries in this matter is very necessary, this is also considering the authority of notaries in providing legal counseling. The emergence of the role of Notaries in providing legal counseling regarding the establishment of Limited Liability Companies raises questions regarding the extent of counseling. the law that can be given by a notary and the legal consequences if the notary does not carry out legal counseling. Notaries are responsible and have the authority to provide legal counseling to parties establishing limited liability companies. This is in accordance with Article 15 paragraph (2) letter e of the Notary Position Law. However, this form of responsibility is not within the realm of an obligation, only in the form of authority alone, so that in this case, if the notary does not exercise his authority in providing legal counseling, it will not have any influence on the deed he makes. There are no sanctions for Notaries who do not provide legal counseling to applicants establishing Limited Liability Companies.